Reproduction biology of the clupeid. Gonialosa manmina (Hamilton, 1822) from the Kaptai Lake Bangladesh - Azadi, MA; Rahman, ASM Sharifur (Chittagong University Journal of Biological Sciences, 2013)
Gonialosa manmina was found to spawn once in a year from February to July in the Kaptai Lake. The fish was found to attain sexual maturity at 80 mm total length. Sex ratio of male and female was 1:2.39 (?2 = 26.25, df = 1, P<0.01). Female dominated significantly over male throughout the year. Seven stages of maturity were determined on the basis of morphological characteristics of gonads and diameter of ova. Fecundity of 24 fishes ranged from 13460 eggs to 56980 eggs with a mean of 32003±12612 eggs. Fecundity factor was 1882 eggs g-1 body weight. Fecundity (F) was highly correlated (P<0.001) with total length (TL), body weight (BW), ovary length (OL) and ovary weight (OW) and the relationships were as follows: F = 1.0080 TL 2.1648 or Log F = 0.0035 + 2.1648 Log TL (r = 0.977, t = 21.49) F = 2.8807 SL 2.0420 or Log F = 0.4595 + 2.0420 Log SL (r = 0.958, t = 15.66) F = 5477.722 BW 0.6332 or Log F = 3.7386 + 0.6332 Log BW (r = 0.990, t = 32.91) F = 12.516 OL 2.2057 or Log F = 1.0975 + 2.2057 Log OL (r = 0.987, t = 28.80) F = 934.544 OW 0.5062 or Log F = 2.9706 + 0.5062 Log OW (r = 0.996, t = 52.28) DOI: http://dx.doi.org/10.3329/cujbs.v3i1.13414 The Chittagong Univ. J. B. Sci.,Vol. 3(1&2):139-148, 2008